Parsing for Indian Languages: A Literature Survey - Prajapati, Manisha; Yajnik, Archit (International Journal of Computer Sciences and Engineering, 2025)
Syntactic parsing is an important undertaking which is required for NLP applications including machine interpretation. It is a testing assignment to build up a subjective parser for morphological rich and agglutinative dialects. Syntactic investigation is utilized to comprehend the linguistic structure of a characteristic dialect sentence. It yields all the linguistic data of each word and its constituent. Likewise, issues identified with it assist us with understanding the dialect in a more point by point way. This writing study is preparation to comprehend the distinctive parser advancement for Indian dialects and different methodologies that are utilized to grow such apparatuses and procedures. This paper gives a study of research papers from surely understood diaries and meetings